Cooperation for Mutual Interests: Reinstating U.S. Influence and Indonesia Green Economy Through Green Investment. - Angdreas, Kevin (INDEF - Institute for Development of Economics and Finance, 2023)
This article is dissecting the dynamism of environmental sentiment in international political economy that currently on the rise, in particular with the United States and Indonesia. This article explores the United States as a superpower country post-President Donald Trump, and the challenges arise and its response during President Joe Biden presidency. Moreover, this paper further examines Indonesia as a developing country that has a great potential of decarbonization on how to put it into practice, while maintain economic development. Seeing the interests of both countries could cross-cut, the paper analyze the potential of environmental-economic cooperation that can deepen bilateral relation. Three theories apply to put into practice: Green Theory; Green Capitalism; and Corporatism. The findings of the paper largely on how the foreign policy of the United States to be the pioneer in decarbonization can be accommodated by Indonesia. However, the decarbonization in Indonesia, facilitated by the United States does not immediately ignite regressive economic development. Instead, it is an opportunity for Indonesia to start in sustainable green economy. The multilateralism approach of the United States, followed by the opportunity of Green Capitalism and Corporatism by Indonesia could benefit, deepen, and strengthen relation between both countries. Keywords: Green Investment, Green Economy, Indonesia, United States, Multilateralism JEL : F59, P33, Q56